Disentangling complete and incomplete fusion events in 12C + 169Tm reaction by spin-distribution measurements. (23rd December 2020) - Sood, Arshiya; Thakur, Swati; Sharma, Arzoo; Sharma, Vijay R; Yadav, Abhishek; Sharma, Manoj K; Singh, B P; Kumar, R; Bhowmik, R K; Singh, Pushpendra P
Abstract: The spin-distributions of different reaction products populated via x n and α /2 αx n channels in C 12 + Tm 169 system have been measured at E lab ≈ 6, 7 and 7.5 MeV A −1 to disentangle complete and incomplete fusion events. Particle (p, α )- γ -coincidences were recorded to identify evaporation residues channel-by-channel. The spin-distributions of fusion evaporation and direct- α -emitting channels are found to be distinct corroborating the involvement of entirely different reaction dynamics in their production, respectively termed as complete (CF) and incomplete fusion (ICF). The values of mean input angular momenta, obtained from the analysis of the spin-distributions, involved in ICF- α /2 α xn channels are estimated to be larger than that observed in CF- xn / α xn channels. For ICF- α /2 αxn channels, the multiplicity of fast- α particle emission increases with the magnitude of input angular momentum imparted into the system. The CF residues display a population of broad spin range while the ICF residues are confined to a narrow spin range generally localized in the higher spin states. Findings of the present work conclusively demonstrate the possibility to populate high spin states in final reaction products using ICF, which are otherwise not accessible. Further, an attempt has been made to study the variation of input angular momentum with the choice of different entrance-channel parameters. It has been observed that the value of input angular momentum involved in ICF- α /2 α xn channels increases with the deformation and entrance-channel mass-asymmetry parameter, indicating strong entrance-channel dependence of ICF dynamics.